Best Practice No 173: Clinical and laboratory investigation of adult spontaneous hypoglycaemia. Issue 9 (27th August 2003) - Gama, R; Teale, J D; Marks, V
Abstract : Adult spontaneous hypoglycaemia is not a diagnosis per se but a manifestation of a disease. Although rare, it is important to identify spontaneous hypoglycaemia and its causes because treatment may be preventative or curative. Hypoglycaemia can occur as an epiphenomenon in many serious diseases. It is sufficient to recognise the disease's association with hypoglycaemia and then take appropriate action to prevent the recurrence of hypoglycaemia. In investigating apparently healthy individuals, common pitfalls to avoid are: failure to recognise subacute neuroglycopenia clinically; failure to document hypoglycaemia adequately during symptoms; failure to measure pancreatic hormones, counter-regulatory hormones, and ketones in hypoglycaemic samples; failure to recognise pre-analytical and analytical limitations of laboratory assays; and failure to abandon obsolete and inappropriate investigations. Providing these caveats are met, appropriate laboratory and radiological investigations will almost always uncover the cause of spontaneous hypoglycaemia.